Unveiling the cognitive scaffold: Metacognitive correlates of academic resilience in biology learners - Salwa Alya Gina; Romy Faisal Mustofa; Rinaldi Rizal Putra (University of Muhammadiyah Malang, 2024)
Good metacognitive allows individuals to more easily adapt to changes in the learning environment and face challenges that arise. They tend to be more flexible in changing their learning strategies according to new needs and situations. The aim of this research is to determine the correlation between metacognitive and the academic resilience of students concentrating on biology subjects at State of Senior High School 1 Tasikmalaya. This research was carried out from January to March 2024. The method used was correlational with a population of 950 students. Sampling was carried out using a quota sampling technique, that 10% of the population was taken which represents the research characteristics of 211 students. The study instruments used consisted of 3 validated instruments, including the Metacognitive Awareness Inventory (MAI) and Academic Resilience 30 (ARS-30). The data were analyzed using a bivariate correlation regression test. Based on the study results, it shows that there is a correlation between metacognitive and (R= 0.792; R2 = 0.627). The Effective Contribution (EC) given by metacognitive to academic resilience, is 15.7%. So, it could be concluded that the correlation between metacognitive to students' academic resilience in biology subjects at State of Senior High School 1 Tasikmalaya is in the strong category because it is in the regression criteria between 0.60 – 0.799.